2010
DOI: 10.1080/10503300903476708
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating client change: Principles based upon the experience of eminent psychotherapists

Abstract: Eminent therapists across psychotherapy meta-orientations were asked to describe the processes by which they facilitate change in psychotherapy. A grounded theory analysis of these interviews was conducted. Safety within the psychotherapeutic relationship was identified as a central element in creating client change to the extent that in-session risk taking was important in that orientation. As well, common processes across orientation in structuring new awareness emerged as a core finding. Patterns were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 27 publications
1
35
1
1
Order By: Relevance
“…Most therapists struggled with disclosure as, even with good intentions; disclosure might not necessarily be helpful for clients (Bottrill et al ., ). Hence, therapists should actively ensure that disclosures are used in a therapeutic manner by taking into account clients’ needs and should, otherwise, protect the client–therapist boundary (Audet and Everall, ; Levitt and Williams, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most therapists struggled with disclosure as, even with good intentions; disclosure might not necessarily be helpful for clients (Bottrill et al ., ). Hence, therapists should actively ensure that disclosures are used in a therapeutic manner by taking into account clients’ needs and should, otherwise, protect the client–therapist boundary (Audet and Everall, ; Levitt and Williams, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since safety in the psychotherapeutic relationship has been viewed as central to the development of positive change (Levitt & Williams, 2010), psychologists are encouraged to use appropriate methods of self-exploration and self-education (e.g., consultation, study, and formal continuing education) to identify and ameliorate implicit and explicit biases about homosexuality and bisexuality. In doing so, psychologists strive to be aware of how their own background and personal factors, such as gender, sexual orientation, heterosexism, and religious ideology, may influence their assessment and treatment of gay, lesbian, and bisexual clients (T. Israel, Gorcheva, Walther, Sulzner, & Cohen, 2008;Morrow, 2000).…”
Section: Guideline 4 Psychologists Are Encouraged To Recognize How Tmentioning
confidence: 99%
“…Clinical research has also consistently demonstrated that safety in a therapeutic relationship is critical for positive change (Levitt & Williams, 2010). Mental health providers are uniquely positioned to help their clients feel safe by seeking to recognize and mitigate the effects of stigma experienced by their CNM clients.…”
Section: Therapeutic Alliances and Cnm Minority Stressmentioning
confidence: 99%
“…Though therapists can support people in CNM relationships, their ability to do so may hinge on using affirming practices to build a positive therapeutic relationships (cf. Corey, Schneider-Corey, & Callanan, 1993;Levitt & Williams, 2010). The current literature guiding therapy with individuals in CNM relationships relies on first-person experiences and small samples (e.g., Bairstow, 2016;Girard & Brownlee, 2015;Weitzman, 2006;Weitzman, Davidson, & Phillips, 2012;Zimmerman, 2012).…”
Section: The Present Studymentioning
confidence: 99%